Beetroot-based gel supplementation improves handgrip strength and forearm muscle O2 saturation but not exercise tolerance and blood volume in jiu-jitsu athletes - Vieira de Oliveira, G.; Diniz do Nascimento, L. A.; Volino-Souza, M.; de Souza Mesquita, J.; Silveira Alvares, T. (Applied Physiology, Nutrition, and Metabolism, 2018)
The ergogenic effect of beetroot on the exercise performance of trained cyclists, runners, kayakers, and swimmers has been demonstrated. However, whether or not beetroot supplementation presents a beneficial effect on the exercise performance of jiu-jitsu athletes remains inconclusive. Therefore, the present study assessed the effect of beetroot-based gel (BG) supplementation on maximal voluntary contraction (MVC), exercise time until fatigue (ETF), muscle O2 saturation (SmO2), blood volume (tHb), and plasma nitrate and lactate in response to handgrip isotonic exercise (HIE) in jiu-jitsu athletes. In a randomized, crossover, double-blind design, 12 jiu-jitsu athletes performed 3 sets of HIE at 40% of the MVC until fatigue after 8 days (the eighth dose was offered 120 min previous exercise) of BG supplementation or a nitrate-depleted gel (PLA), and forearm SmO2 and tHb were continuously monitored by using near-infrared spectroscopy. Blood samples were taken before, immediately after exercise, and 20 min after exercise recovery in the PLA and BG conditions. MVC was evaluated at baseline and 20 min after HIE. There was a significant reduction in ?MVC decline after HIE in the BG condition. Forearm SmO2 during exercise recovery was significantly greater only after BG supplementation. No significant difference in ETF and tHb were observed between both BG and PLA in response to HIE. Plasma nitrate increased only after BG, whereas the exercise-induced increase in plasma lactate was significantly lower in BG when compared with PLA. In conclusion, BG supplementation may be a good nutritional strategy to improve forearm SmO2 and prevent force decline in response to exercise in jiu-jitsu athletes.